DCT IMAGE COMPRESSION USING SLIDING RLETECHNIQUE - Baithoon, Nushwan (Iraqi Journal of Science, 2024)
The discrete cosine transform (DCT) is a method for converting a signal intoplain frequency components. It is extensively used in image compression. In thispaper a new technique is proposed, namely SRLE (Sliding Run Length Encoding)which is based on a lossy compression, and used to enhance image datacompression.Image quality is measured impartially, using peak signal-to-noise ratio (PSNR) orpicture quality scale, and individually using perceived image quality withcompression factor (CF) being the main theme of this paper, taking intoconsideration the preservation of well PSNR outputs.The performance of DCT compression generally degrades low bit-rates mainlybecause of the underlying block-based DCT scheme. Experimental resultsdemonstrate the effectiveness of the SRLE approach, in terms of PSNR, CF andexecution time, over different mechanisms used with DCT image compression. Thenew technique also proved to have favourable results in terms of PSNR and CFwhen compared with some wavelet based image compression.